Biceps femoris long head morphology in youth competitive alpine skiers is associated with age, biological maturation and traumatic lower extremity injuries - Fitze, Daniel P.; Franchi, Martino V.; Fröhlich, Stefan; Frey, Walter O.; Spörri, Jörg (Frontiers in Physiology, 2022)
Lower extremity injuries are common in competitive alpine skiers, and the knee and lower leg are often affected. The hamstring muscles, especially the biceps femoris long head (BFlh), can stabilize the knee and the hip and may counteract various adverse loading patterns during typical mechanisms leading to severe lower extremity injuries. The aim of the present study was to describe BFlh morphology in youth competitive alpine skiers in relation to sex, age and biological maturation and to investigate its association with the occurrence of traumatic lower extremity injuries in the upcoming season. Ninety-five youth skiers underwent anthropometric measurements, maturity offset estimations and ultrasound assessment, followed by 12-month prospective injury surveillance. Unpaired t tests showed that the two sexes did not differ in BFlh morphology, including fascicle length (Lf), pennation angle (PA), muscle thickness (MT) and average anatomical cross-sectional area (ACSAavg). In contrast, U16 skiers had longer fascicles than U15 skiers (9.5 ± 1.3 cm vs. 8.9 ± 1.3 cm, p < 0.05). Linear regression analyses revealed that maturity offset was associated with Lf (R2 = 0.129, p < 0.001), MT (R2 = 0.244, p < 0.001) and ACSAavg (R2 = 0.065, p = 0.007). No association was found between maturity offset and PA (p = 0.524). According to a binary logistic regression analysis, ACSAavg was significantly associated with the occurrence of traumatic lower extremity injuries (Chi-square = 4.627, p = 0.031, R2Nagelkerke = 0.064, Cohen f = 0.07). The present study showed that BFlh morphology is age- and biological maturation-dependent and that BFlh ACSAavg can be considered a relevant modifiable variable associated with lower extremity injuries in youth competitive alpine skiers.